Recycled terephthalic acid and polyester resins comprising the same
Patent Information
- Application Number
- CN202480089712.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-17
- Filing Date
- 2024-11-12
- Publication Date
- 2026-10-16
AI Technical Summary
[0016] Beneficial effects of the present invention
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to recycled terephthalic acid prepared from waste polyester and polyester resins containing the recycled terephthalic acid. Background Technology
[0002] Polyester, with its excellent mechanical strength, heat resistance, transparency, and gas barrier properties, is widely used as a material for beverage filling containers, packaging films, audio-visual films, and industrial materials such as medical fibers and tire cords. In particular, polyester sheets or boards have good transparency and excellent mechanical strength, making them widely used as raw materials for boxes, containers, partitions, shelves, panels, packaging materials, building materials, and interior and exterior materials.
[0003] With the world generating uncontrollable levels of plastic (such as polyester) waste annually, there is growing interest in recycling waste polyester or in recycling processes that utilize waste polyester. Furthermore, countries worldwide have developed regulations and programs for recycling waste plastic resources, including waste polyester. For example, regulations currently under discussion require the use of recycled resins in packaging materials used across various sectors, at a certain percentage or higher.
[0004] In particular, polyethylene terephthalate (PET) is widely used in the manufacture of a variety of products such as films, fibers, bottles, and containers due to its excellent properties in terms of heat resistance, processability, transparency, and non-toxicity. However, most of them end up in landfills or incinerators after use; therefore, research into recycling or regeneration processes using it continues.
[0005] For example, Korean Patent Application Publication No. 1997-0042469 discloses a technique for preparing terephthalic acid, which involves hydrolyzing waste polyethylene terephthalate with an alkaline aqueous solution to obtain a slurry of alkali metal and alkaline earth metal salts of terephthalic acid, and then neutralizing the slurry with acid. As a result of the hydrolysis reaction, terephthalate salts are produced instead of terephthalic acid, and a neutralization step with added acid is necessary to convert them to terephthalic acid. The problem is that the resulting byproducts generate environmental pollutants or produce large amounts of acid treatment wastewater. Furthermore, as mentioned above, in the case of terephthalic acid being converted from terephthalate salts, the purity is low due to the difficulty in removing impurities, and physical properties such as color characteristics are poor, resulting in poor quality.
[0006] [Existing Technical Documents]
[0007] [Patent Literature]
[0008] (Patent Document 1) Korean Patent Application Publication No. 1997-0042469 Detailed Implementation
[0009] Technical issues
[0010] Therefore, the present invention aims to provide terephthalic acid of excellent quality produced in an environmentally friendly manner through alcoholysis and hydrolysis of waste polyester, and polyester resin containing the terephthalic acid.
[0011] Solution to the problem
[0012] The recycled terephthalic acid according to embodiments of the present invention is obtained by alcoholysis and hydrolysis of waste polyester, and has a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer.
[0013] According to another embodiment of the invention, the polyester resin comprises recycled terephthalic acid obtained by alcoholysis and hydrolysis of waste polyester and having a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer, and the polyester resin has a difference (chromaticity L - chromaticity b) between a chromaticity L value of greater than 83 and a chromaticity b value as measured in transmission mode of a spectrophotometer for a sample with a thickness of 6 mm.
[0014] The article according to another embodiment of the invention comprises polyester resin.
[0015] A method for preparing polyester resin according to another embodiment of the present invention includes: alcoholystolysis and hydrolysis of waste polyester to prepare recycled terephthalic acid; mixing the recycled terephthalic acid with a diol component to prepare a preliminary composition; esterifying the preliminary composition; and polycondensing the esterification product, wherein the recycled terephthalic acid has a color value b of less than 2.
[0016] Beneficial effects of the present invention
[0017] Since the recycled terephthalic acid according to embodiments of the present invention is obtained through alcoholysis and hydrolysis of waste polyester, and has a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer, it is environmentally friendly, has low pigment residue and low yellowness index, and has very low metal impurity content, thus producing excellent quality.
[0018] Therefore, polyester resins containing recycled terephthalic acid exhibit excellent quality even without additional terephthalic acid besides recycled terephthalic acid. Specifically, conventionally recycled terephthalic acid prepared from waste polyester has poor physical properties, such as color characteristics. Furthermore, polyester resins prepared using such recycled terephthalic acid alone as an acid component are of lower quality, making them difficult to use. Therefore, to ensure the properties of polyester resins, the content of recycled terephthalic acid should be reduced and used in small quantities, or it should be used in combination with commercially available terephthalic acid.
[0019] However, the polyester resin according to embodiments of the present invention contains recycled terephthalic acid with excellent quality. Although it is prepared from waste polyester, it has low pigment residue, low yellowness index, and very low metal impurity content. Therefore, even when the polyester resin contains only recycled terephthalic acid as an acid component or contains recycled terephthalic acid in a higher amount than in the prior art, the polyester resin still has excellent quality.
[0020] Best way to carry out the invention
[0021] The present invention will be described in detail below. The present invention is not limited to the disclosure given below; it can be modified in various forms without altering its essential elements.
[0022] Throughout this specification, when a part is referred to as "containing" an element, it should be understood that other elements may be included, rather than excluded, unless otherwise expressly stated.
[0023] Unless otherwise specified, all figures and expressions relating to the amounts of components, reaction conditions, etc., used herein should be understood to be modified by the term “about”.
[0024] Throughout this specification, the terms "first," "second," etc., are used to describe various components. However, components should not be limited by the terms. Terms are used only to distinguish one component from another.
[0025] Recycled terephthalic acid
[0026] The recycled terephthalic acid according to embodiments of the present invention is obtained by alcoholysis and hydrolysis of waste polyester, and has a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer.
[0027] Alcoholization and hydrolysis will be described in detail below.
[0028] The recycled terephthalic acid according to embodiments of the present invention has a chromaticity b of less than 2, as measured in reflectance mode of a spectrophotometer. For example, the chromaticity b of the recycled terephthalic acid can be 1.9 or less, 1.8 or less, 1.6 or less, 1.4 or less, 1.2 or less, or 1 or less, as measured in reflectance mode of a spectrophotometer. Since the above-mentioned range of chromaticity b values is comparable to the range of terephthalic acid typically produced in petrochemical processes, the recycled terephthalic acid meeting the above-mentioned chromaticity b range not only has a low yellowness index but also exhibits excellent quality due to the well-purified monomers.
[0029] Chromaticity b is a chromaticity coordinate system established by the International Commission on Illumination (CIE), where chromaticity is represented by L (lightness), a (green to red complementary color), and b (yellow to blue complementary color). It can be measured using a spectrophotometer.
[0030] More specifically, a Varian Cary 5 UV / Vis / NIR spectrophotometer equipped with a diffuse reflectance accessory capable of measuring chromaticity and lightness was used to measure recycled terephthalic acid in reflectance mode with a luminescent body of D65 and an observer angle of 2° to obtain data, which was then processed by the chromaticity analysis device in Grams / 32 software to calculate the chromaticity b value.
[0031] Recycled terephthalic acid is obtained through a purification process and can have a pigment residue of 10% or less according to Equation 1 below.
[0032] [Equation 1]
[0033] In Equation 1, B1 is the area of the absorbance curve obtained using a UV-vis spectrophotometer at 400 nm to 800 nm after diluting recycled terephthalic acid to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP), and B2 is the area of the absorbance curve obtained in the same manner as above for recycled terephthalic acid obtained by the same preparation process as above but without purification.
[0034] In the method for preparing recycled terephthalic acid, the B1 of the recycled terephthalic acid produced by performing a purification step, or a purification and concentration step, can be measured. In the method for preparing recycled terephthalic acid, the B2 of the recycled terephthalic acid produced without a purification step, or by performing only a concentration step, can be measured.
[0035] Pigment residue rate refers to the amount of additives such as colorants, pigments, and dyes remaining in the composition. The lower the pigment residue rate, the lower the content of additives such as colorants, pigments, and dyes, indicating higher purity.
[0036] For example, the pigment residue of recycled terephthalic acid may be 9% or less, 8% or less, 7% or less, 5% or less, or 4% or less.
[0037] As specific examples, when dimethyl sulfoxide (DMSO) is used as the solvent for diluting recycled terephthalic acid, the pigment residue percentage according to Equation 1 above can be 2% or less, 1% or less, or 0.5% or less. When dimethylformamide (DMF) is used, the pigment residue percentage according to Equation 1 above can be 2% or less, 1% or less, or 0.5% or less. When methylpyrrolidone (NMP) is used, the pigment residue percentage according to Equation 1 above can be 2% or less, 1% or less, or 0.5% or less.
[0038] The purification and concentration processes will be described in detail below.
[0039] Furthermore, when recycled terephthalic acid is diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP) and measured with a spectrophotometer, the yellowness index (YI) can be less than 2, 1.9 or less, 1.8 or less, or 1.7 or less.
[0040] As specific examples, when recycled terephthalic acid is diluted to a 5% concentration in dimethyl sulfoxide (DMSO) and measured with a spectrophotometer, the yellowness index can be 2 or less, 1.8 or less, or 1.6 or less. When recycled terephthalic acid is diluted to a 5% concentration in dimethylformamide (DMF) and measured with a spectrophotometer, the yellowness index can be 2 or less, 1.9 or less, or 1.6 or less. When recycled terephthalic acid is diluted to a 5% concentration in methylpyrrolidone (NMP) and measured with a spectrophotometer, the yellowness index can be 2 or less, 1.7 or less, or 1.6 or less.
[0041] In methods for preparing recycled terephthalic acid, the yellowness index of the recycled terephthalic acid produced by purification steps or purification and concentration steps can be measured.
[0042] According to embodiments of the present invention, when measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), recycled terephthalic acid can have a total metal content of less than 100 ppm. Specifically, recycled terephthalic acid, more specifically, recycled terephthalic acid prepared by purification steps or purification and concentration steps, can have a low content of insoluble impurities (such as metals).
[0043] For example, when measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), recycled terephthalic acid can have a total metal content of 90 ppm or less, 80 ppm or less, 65 ppm or less, 50 ppm or less, 35 ppm or less, less than 30 ppm, 15 ppm or less, 9 ppm or less, 7 ppm or less, 5 ppm or less, or 1 ppm or less.
[0044] Furthermore, when measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), recycled terephthalic acid can have a total Sb, Ti, and Zn content of less than 30 ppm. For example, the Sb, Ti, and Zn in recycled terephthalic acid may be harmful to humans or may act as catalysts for reactions or side reactions in subsequent polymerization processes, and their total content may be 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less.
[0045] For example, when measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Sb content in recycled terephthalic acid can be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less relative to the total weight of the recycled terephthalic acid.
[0046] When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Ti content in recycled terephthalic acid can be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less relative to the total weight of the recycled terephthalic acid.
[0047] When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Zn content in recycled terephthalic acid can be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less relative to the total weight of the recycled terephthalic acid.
[0048] Polyester resin
[0049] According to another embodiment of the invention, the polyester resin comprises recycled terephthalic acid obtained by alcoholysis and hydrolysis of waste polyester and having a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer, and the polyester resin has a difference (chromaticity L - chromaticity b) between a chromaticity L value of greater than 83 and a chromaticity b value as measured in transmission mode of a spectrophotometer for a sample with a thickness of 6 mm.
[0050] Polyester resins contain recycled terephthalic acid.
[0051] Specifically, the content of recycled terephthalic acid can be from 0.1% to 55% by weight based on the total weight of the polyester resin. For example, the content of recycled terephthalic acid can be from 0.5% to 55% by weight, 1% to 52% by weight, 1.5% to 50% by weight, 2% to 48% by weight, 3% to 46% by weight, 3.5% to 45% by weight, or 10% to 50% by weight based on the total weight of the polyester resin.
[0052] In addition, for a sample with a thickness of 6 mm, the polyester resin has a difference between the chromaticity L value and the chromaticity b value (chromaticity L - chromaticity b) as measured in the transmission mode of a spectrophotometer, which is greater than 83, 84 or greater, 85 or greater, 88 or greater, 89 or greater, or 90 or greater.
[0053] More specifically, polyester resin samples with a thickness of 6 mm were prepared. Using a Varian Cary 5 UV / Vis / NIR spectrophotometer equipped with a diffuse reflectance accessory capable of measuring chromaticity and lightness, the sample was measured in transmission mode with a luminaire at D65 and an observation angle of 2° to obtain data. The data were then processed using the chromaticity analysis device in Grams / 32 software to calculate the Henry chromaticity L, chromaticity a, and chromaticity b values. The chromaticity L - chromaticity b value, i.e., the difference between the chromaticity L and chromaticity b values, was then calculated.
[0054] Furthermore, the polyester resin can have an intrinsic viscosity (IV) of 0.5 dl / g to 1.3 dl / g. For example, the intrinsic viscosity (IV) of the polyester resin can be 0.5 dl / g to 1.2 dl / g, 0.55 dl / g to 1 dl / g, or 0.6 dl / g to 0.95 dl / g.
[0055] As an embodiment of the present invention, the polyester resin may comprise a diacid component and a diol component. Specifically, the polyester resin may comprise only recycled terephthalic acid as the diacid component, or it may comprise another diacid component and recycled terephthalic acid. More specifically, the polyester resin is a copolymer of the diacid component and the diol component, and it may comprise repeating units derived from the diacid component and repeating units derived from the diol component.
[0056] Conventionally, recycled terephthalic acid, prepared from waste polyester, exhibits poor physical properties such as color characteristics, making it difficult to use alone as an acid component in polyester resin raw materials. However, the polyester resin according to embodiments of the present invention is prepared using recycled terephthalic acid; therefore, even when the content of recycled terephthalic acid is increased compared to conventional methods, sufficient physical properties can be ensured. Therefore, the polyester resin according to embodiments of the present invention may contain only recycled terephthalic acid, or may contain recycled terephthalic acid and another diacid component to enhance physical properties, etc.
[0057] The diacid component may include at least one selected from the group consisting of: terephthalic acid (TPA), isophthalic acid (IPA), dimethyl isophthalate, bis(2-hydroxyethyl) terephthalate, recycled bis(2-hydroxyethyl) terephthalate (r-BHET), phthalic acid, dimethyl terephthalate, phthalic anhydride, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylic acid, biphenyl dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, dimethyl 1,4-cyclohexanedicarboxylic acid, dimethyl 1,3-cyclohexanedicarboxylic acid, sebacic acid, succinic acid, isodexylsuccinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid, and azelaic acid.
[0058] In addition, the diol compound may contain at least one selected from the group consisting of: isosorbide (ISB), recycled isosorbide (r-ISB), ethylene glycol (EG), recycled ethylene glycol (r-EG), 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-methylene-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-isopropyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol. Alcohols, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, cyclohexanediol (CHDM) and its derivatives, recycled cyclohexanediol (r-CHDM), diethylene glycol (DEG), recycled diethylene glycol (r-DEG), neopentyl glycol (NPG) and recycled neopentyl glycol (r-NPG).
[0059] Specifically, the polyester resin may contain recycled terephthalic acid and diacid components. In this case, the molar ratio of recycled terephthalic acid to diacid components may be 1:0.01 to 3.5, 1:0.02 to 3.3, 1:0.03 to 3.0, or 1:0.05 to 2.6.
[0060] According to embodiments of the present invention, the polyester resin may further comprise at least one additive selected from the group consisting of: colorants, crystallizers, oxidative stabilizers, and branching agents.
[0061] Colorants are additives used to enhance the color characteristics of polyester resins. Commonly used colorants such as cobalt acetate and cobalt propionate can be used as colorants, provided that the effects of the invention are not compromised.
[0062] Specifically, the colorant can be cobalt acetate, cobalt propionate, anthraquinone-based compounds, perylene-based compounds, azo-based compounds, and methine-based compounds.
[0063] Furthermore, based on the total weight of the polyester resin, the polyester resin may contain a colorant in an amount ranging from 0.1 ppm to 30 ppm. For example, based on the total weight of the polyester resin, the colorant may be used in amounts ranging from 0.2 ppm to 30 ppm, 0.5 ppm to 25 ppm, 0.6 ppm to 23 ppm, or 0.8 ppm to 20 ppm. When the content of the colorant meets the above ranges, its color characteristics can be sufficiently enhanced without impairing the mechanical properties of the polyester resin.
[0064] The crystallizing agent may contain at least one selected from the group consisting of: crystal nucleating agents, UV absorbers, polyolefin resins, polyamide resins, and polyalkylene resins.
[0065] Furthermore, based on the total weight of the polyester resin, the polyester resin may contain a crystallizing agent in an amount ranging from 0.1 ppm to 10 ppm. For example, based on the total weight of the polyester resin, the crystallizing agent may be used in amounts of 0.2 ppm to 8 ppm, 0.5 ppm to 6 ppm, 1 ppm to 10 ppm, 2 ppm to 8 ppm, 3 ppm to 6 ppm, or 4 ppm to 6 ppm. When the content of the crystallizing agent meets the above ranges, heat resistance and impact strength can be enhanced.
[0066] Oxidation stabilizers may include at least one selected from the group consisting of hindered phenol-based oxidation stabilizers, phosphite-based oxidation stabilizers, and thioether-based oxidation stabilizers.
[0067] Furthermore, based on the total weight of the polyester resin, the polyester resin may contain an oxidation stabilizer in amounts ranging from 50 ppm to 2,500 ppm. For example, based on the total weight of the polyester resin, the oxidation stabilizer may be used in amounts of 50 ppm to 2,300 ppm, 60 ppm to 2,200 ppm, 80 ppm to 2,100 ppm, 100 ppm to 2,000 ppm, or 100 ppm to 1,500 ppm. When the content of the oxidation stabilizer meets the above ranges, it can effectively prevent the reduction of intrinsic viscosity that may occur in subsequent processes, and it can also prevent the reduction of physical properties such as impact strength.
[0068] The branching agent may contain at least one selected from the group consisting of trimellitic anhydride, trimethylolpropane, and trimellitic acid.
[0069] Furthermore, based on the total weight of the polyester resin, the polyester resin may contain a branching agent in amounts ranging from 100 ppm to 2,500 ppm. For example, based on the total weight of the polyester resin, the branching agent may be used in amounts of 200 ppm to 2,500 ppm, 300 ppm to 2,300 ppm, 500 ppm to 2,300 ppm, 1,000 ppm to 2,500 ppm, 1,500 ppm to 2,300 ppm, or 1,800 ppm to 2,100 ppm. When the content of the branching agent meets the above ranges, the intrinsic viscosity can be controlled more effectively within a specific range, thereby also enhancing physical properties such as impact strength.
[0070] Products
[0071] The article according to another embodiment of the invention comprises polyester resin.
[0072] Articles can be obtained by molding resin containing polyester resin using molding methods such as extrusion and injection molding. Articles can be films (or sheets) or components used in the automotive, electrical, and electronic fields.
[0073] In addition, articles may include labels or caps for various containers (such as plastics) or packaging materials.
[0074] Method for preparing polyester resin
[0075] A method for preparing polyester resin according to another embodiment of the present invention includes: alcoholystolysis and hydrolysis of waste polyester to prepare recycled terephthalic acid; mixing the recycled terephthalic acid with a diol component to prepare a preliminary composition; esterifying the preliminary composition; and polycondensing the esterification product, wherein the recycled terephthalic acid has a color value b of less than 2.
[0076] The steps of alcoholysis and hydrolysis of waste polyester to prepare recycled terephthalic acid
[0077] A method for preparing polyester resin according to another embodiment of the present invention includes: alcoholystolysis and hydrolysis of waste polyester to prepare recycled terephthalic acid.
[0078] Specifically, the steps for preparing recycled terephthalic acid may include: (1) alcoholystolysis of waste polyester with an alcohol having four or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1; and (2) hydrolysis of the liquid composition.
[0079] [Formula 1]
[0080] In Formula 1, R1 is an alkyl group having four or more carbon atoms.
[0081] Alcohololysis step (1)
[0082] A method for preparing recycled terephthalic acid according to another embodiment of the present invention comprises: alcoholystopping waste polyester with an alcohol having four or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1.
[0083] Waste polyester can be obtained by crushing or melting waste polyester products. For example, waste polyester can be obtained by crushing used, recycled and separated polyester products or converting them into pellets (post-consumer recycled materials; PCR), or by polyester waste (post-industrial recycled materials; PIR) that may be generated during molding processes such as polyester films, fibers, containers, etc., such as defective products or waste, but is not limited to these.
[0084] In addition, the number of carbon atoms in an alcohol can be 4 or more, 6 or more, 8 or more, 10 or more, or 12 or more, and can be 4 to 14, 4 to 13, 4 to 10, 4 to 8, 6 to 12, 8 to 14, or 8 to 13.
[0085] Since the alcoholysis of waste polyester is carried out using alcohols with the aforementioned number of carbon atoms, it can be conducted at lower temperatures and pressures compared to conventional processes using waste polyester that operate at high temperatures and pressures. Furthermore, intermediates, i.e., the alcoholysis products, can be produced in liquid form. Additionally, the alcoholysis reaction rate can be increased when the number of carbon atoms in the alcohol meets the aforementioned range.
[0086] Furthermore, alcohols can have boiling points ranging from 100°C to 290°C. For example, the boiling points of alcohols can be 100°C to 280°C, 100°C to 260°C, 100°C to 230°C, 110°C to 190°C, or 180°C to 290°C. When the boiling point of the alcohol meets the above range, ethylene glycol formed as a byproduct during alcoholysis can be more easily removed or recovered in subsequent processes, thereby further improving processability. In particular, in recent years, there has been a trend in the field of using polyester as a raw material to use various monomer materials; therefore, this method can be readily used to remove various diol-type monomers used in waste polyester products (such as waste plastic products).
[0087] The weight ratio of waste polyester to alcohol can be from 1:1 to 10. For example, the weight ratio of waste polyester to alcohol can be from 1:1 to 8, 1:1 to 6, 1:1 to 4, 1:1 to 3.5, 1:1.1 to 3.3, 1:2 to 4, or 1:2 to 3.5.
[0088] Furthermore, the alcoholysis reaction can be carried out at temperatures ranging from 160°C to 280°C and pressures ranging from 1 bar to 40 bar for 0.5 hours to 24 hours. For example, the alcoholysis reaction can be carried out at temperatures ranging from 165°C to 280°C, 165°C to 270°C, 180°C to 270°C, 190°C to 250°C, 200°C to 265°C, 220°C to 265°C, 240°C to 260°C, or 245°C to 260°C and pressures ranging from 1 bar to 38 bar, 1 bar to 33 bar, 1 bar to 28 bar, 1 bar to 24 bar, 2 bar to 40 bar, 3 bar to 35 bar, or 5 bar to 30 bar for 0.5 hours to 22 hours, 1 hour to 15 hours, 1.5 hours to 10 hours, 2 hours to 8 hours, or 2 hours to 6 hours.
[0089] In step (1), an alcoholysis catalyst may be added. Specifically, the alcoholysis reaction can proceed smoothly as a non-catalytic reaction without the use of an alcoholysis catalyst, making it environmentally friendly. In particular, when the content of insoluble metals in the waste polyester is high, the non-catalytic reaction may be beneficial for the effective treatment and removal of impurities. Furthermore, from an energy perspective, the addition of an alcoholysis catalyst in step (1) can improve processability by enhancing reactivity.
[0090] The alcoholysis catalyst can be a metal acetate, alkali metal salt, or hydroxyl salt.
[0091] More specifically, the alcoholysis catalyst may contain at least one cation selected from the group consisting of alkali metal ions such as Li. + Na + K + and Cs + Alkaline earth metal ions such as Be2+ Mg 2+ Ca 2+ and Ba 2+ Ammonium ions, such as NH4+ 4+ and NR 4 + (where R is an alkyl group), and Zn 2+ ; or at least one anion selected from the group consisting of: OH- - OR - (where R is an alkyl group), HCO3 - CO3 2- Benzoate ions (C7H5O2) - ), 4-alkoxycarbonylbenzoate ion, acetate ion, and terephthalate ion. R can be an alkyl group having 1 to 10 carbon atoms or an alkyl group having 1 to 5 carbon atoms.
[0092] For example, the alcoholysis catalyst may contain at least one selected from the group consisting of: Zn(OAC)2, Co(OAc)2, Mn(OAc)2, Mg(OAc)2, Ca(OAc)2, Ba(OAc)2, LiOAc, NaOAc, KOAc, Zn(OAC)2·2H2O, Co(OAc)2·4H2O, Pb(OAc)2, Mn(OAc)2·4H2O, Mg(OAc)2·4H2O, Pd(OAc)2, Ti(OBu)4, Ti(OiPr)4, GeO2, Al(OiPr)3, Na2CO3, K2CO3, dibutyltin oxide (IV), stannous octoate, titanium phosphate, and terephthalic acid.
[0093] Furthermore, the amount of alcoholysis catalyst added can be from 10 ppm to 10,000 ppm, depending on the total weight of the waste polyester. For example, the amount of alcoholysis catalyst added can be from 10 ppm to 9,000 ppm, 15 ppm to 8,000 ppm, 20 ppm to 6,000 ppm, 50 ppm to 3,500 ppm, 100 ppm to 1,500 ppm, 150 ppm to 1,000 ppm, 180 ppm to 500 ppm, or 200 ppm to 450 ppm, depending on the total weight of the waste polyester.
[0094] According to embodiments of the present invention, a liquid composition comprising a compound represented by Formula 1 is prepared by alcoholysis. Specifically, the composition is liquid at room temperature, and the liquid composition is a composition produced by an alcoholysis reaction.
[0095] The liquid composition may contain a compound represented by Formula 1 below.
[0096] [Formula 1]
[0097] In Formula 1, R1 is an alkyl group having four or more carbon atoms.
[0098] Specifically, R1 can be butyl, n-butyl, isobutyl, tert-butyl, sec-butyl, 1-methyl-butyl, 1-ethyl-butyl, pentyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, 2-ethylbutyl, hexyl, 1-methylhexyl, 2-ethyl-1-hexyl, heptyl, n-heptyl, 1-methylheptyl, octyl, n-octyl, isooctyl, tert-octyl, 2-propylpentyl, n-nonyl, 2,2-dimethylheptyl, 1-ethyl-propyl, 1,1-dimethylpropyl, isohexyl, 2-methylpentyl, 4-methylhexyl, 5-methylhexyl, decyl, undecyl, dodecyl, tridecyl, or tetradecyl.
[0099] Specifically, the liquid composition may contain unreacted alcohol and ethylene glycol (EG) as a byproduct. More specifically, the liquid composition may contain a compound represented by Formula 1, ethylene glycol (EG) formed as a byproduct via alcoholysis, unreacted alcohol, and oligomers.
[0100] For example, the liquid composition may contain a compound represented by Formula 2 below, and the oligomer may contain a compound represented by Formula 3 below.
[0101] [Equation 2]
[0102] [Formula 3]
[0103] In Formulas 2 and 3, R1 is an alkyl group having 4 or more carbon atoms, and n is an integer of 1 or greater.
[0104] According to embodiments of the present invention, the liquid composition may contain unreacted alcohol and ethylene glycol as a byproduct, and the content of the compound represented by Formula 1 in the liquid composition may be 70% or more on a molar basis. For example, the content of the compound represented by Formula 1 in the liquid composition prepared by alcoholysis may be 72% or more on a molar basis, 75% or more on a molar basis, 80% or more on a molar basis, 85% or more on a molar basis, 90% or more on a molar basis, 91% or more on a molar basis, 92% or more on a molar basis, 92.5% or more on a molar basis, 93% or more on a molar basis, 95% or more on a molar basis, 97% or more on a molar basis, 99% or more on a molar basis, or 99.5% or more on a molar basis.
[0105] Furthermore, the oligomer content in the liquid composition may be 15% or less on a molar basis. For example, the oligomer content in the liquid composition may be 11% or less on a molar basis, 8.5% or less on a molar basis, 7% or less on a molar basis, 5% or less on a molar basis, 3% or less on a molar basis, 1% or less on a molar basis, 0.8% or less on a molar basis, 0.4% or less on a molar basis, or 0.1% or less on a molar basis.
[0106] According to another embodiment of the present invention, step (1) may include discharging unreacted alcohol and ethylene glycol as a byproduct.
[0107] Specifically, the alcohol is separated from the discharged mixture of alcohol and ethylene glycol, and the separated alcohol can be recycled as feedstock for alcoholysis. For example, ethylene glycol and unreacted alcohol (excess alcohol) formed as byproducts during alcoholysis are discharged in real time as a gaseous mixture during the alcoholysis reaction, and then fractionated or separated and / or distilled after the reaction to separate them into alcohol and ethylene glycol. The separated alcohol can be introduced into the alcoholysis of step (1) and reused. In this case, the volume and feed rate of the alcohol introduced for reuse can be the same as the volume and discharge rate of the discharged mixture of alcohol and ethylene glycol.
[0108] Furthermore, step (1) may include recovering ethylene glycol as a byproduct of alcoholysis. Specifically, ethylene glycol as a byproduct of alcoholysis can be recovered by fractionation or layer separation of the discharged alcohol and ethylene glycol mixture, and can also be recovered by fractionation or layer separation of the composition prepared in step (1).
[0109] For example, unreacted alcohols and ethylene glycol as a byproduct are discharged in real time as a gaseous mixture during the alcoholysis reaction, and condensed using an external cooling device to recover the ethylene glycol.
[0110] According to embodiments of the present invention, not only can unreacted alcohols and ethylene glycol be separated by simple processes such as fractionation or layer separation, but the separated unreacted alcohols can also be recycled as feedstock for alcoholysis, and the recovered ethylene glycol can be used in other processes. Therefore, processability and reduced process costs are excellent.
[0111] The recovery rate of ethylene glycol can be 65% or higher. For example, the recovery rate of ethylene glycol can be 70% or higher, 76% or higher, 85% or higher, 90% or higher, 93% or higher, 95% or higher, 97% or higher, 98% or higher, 99% or higher, or 99.5% or higher.
[0112] Purification steps
[0113] A method for preparing recycled terephthalic acid according to another embodiment of the present invention may further include purifying the liquid composition prior to step (2) as described below.
[0114] Specifically, the purification step may include adding at least one adsorbent selected from the group consisting of activated carbon, silica gel, alumina, zeolite, and activated clay, or adsorption may be carried out by bed adsorption. More specifically, the adsorbent may be activated carbon, or a mixture of activated carbon and silica gel. For example, the adsorbent may be a mixture of activated carbon and silica gel in a weight ratio of 1:0.5 to 1.5, or 1:0.8 to 1.2, but is not limited thereto.
[0115] The content of the added adsorbent can be from 0.1% to 20% by weight based on the total weight of the liquid composition. For example, the content of the added adsorbent can be from 0.1% to 18% by weight, 0.1% to 15% by weight, 0.1% to 10% by weight, 0.1% to 5% by weight, or 0.1% to 2% by weight based on the total weight of the liquid composition.
[0116] Further purification of the liquid composition using an adsorbent, specifically an adsorbent at a specific feed amount within the aforementioned numerical range, can further improve purity and yield. Specifically, when purifying the liquid composition (i.e., the alcoholysis composition), insoluble impurities (such as metals) that may be present in the alcoholysis composition, or additives (such as colorants and pigments) that may be present in the waste polyester, can be removed more effectively. Therefore, the purity and yield of the final prepared terephthalic acid can be further improved.
[0117] Furthermore, according to another embodiment of the present invention, the method for preparing recycled terephthalic acid may further include a concentration step after the purification step.
[0118] Concentration can be carried out at a temperature of 50°C to 120°C for 0.5 hours to 6 hours. For example, by stirring the purified alcoholysis composition, concentration can be carried out at a temperature of 55°C to 115°C, 60°C to 110°C, 65°C to 105°C, or 75°C to 100°C for 1 hour to 5 hours, 1.5 hours to 4 hours, or 2 hours to 4 hours.
[0119] Furthermore, the purified composition may have a pigment residue of 15% or less according to Equation A below.
[0120] [Equation A]
[0121] In Equation A, A1 is the area of the absorbance curve obtained using a UV-vis spectrophotometer at 400 nm to 800 nm after diluting the purified alcoholysis composition to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP), and A2 is the area of the absorbance curve obtained for the unpurified alcoholysis composition in the same manner as described above.
[0122] For example, the purified alcoholysis composition may have a pigment residue (%) of 13% or less, 11% or less, 10% or less, 8% or less, 6% or less, 5.5% or less, 5% or less, 4.3% or less, or 4% or less according to Equation A.
[0123] As specific examples, when dimethyl sulfoxide (DMSO) is used as the solvent for diluting the alcoholysis reaction composition, the pigment residue percentage according to Equation A above may be 11% or less, 10% or less, or 8.5% or less. When dimethylformamide (DMF) is used, the pigment residue percentage according to Equation A above may be 10.5% or less, 9% or less, or 8.3% or less. When methylpyrrolidone (NMP) is used, the pigment residue percentage according to Equation A above may be 10% or less, 8.5% or less, or 8% or less.
[0124] Hydrolysis reaction step (2)
[0125] The method for preparing recycled terephthalic acid according to an embodiment of the present invention includes hydrolyzing a liquid composition. Specifically, in step (2), the alcoholysis composition (a liquid composition comprising a compound represented by Formula 1 above) prepared in step (1) or the purified alcoholysis composition may be hydrolyzed to prepare recycled terephthalic acid.
[0126] Hydrolysis can be carried out by adding water to the composition. For example, hydrolysis can be carried out by adding water to the alcoholysis composition or the purified alcoholysis composition at a temperature of 180°C to 280°C, 185°C to 280°C, 200°C to 275°C, 220°C to 270°C, or 240°C to 265°C for 0.5 to 24 hours, 1 to 20 hours, 2.5 to 12 hours, or 3 to 8 hours.
[0127] The conventional method of adding metal catalysts such as iron, cobalt, manganese, or nickel to waste polyester and then hydrolyzing it directly with water is environmentally friendly. However, it has low processability because it requires extremely high temperature conditions of 300°C or higher, and the reaction apparatus must also be able to withstand high pressures. In contrast, the method for preparing recycled terephthalic acid according to embodiments of the present invention has excellent processability because the process conditions are improved compared to the prior art.
[0128] Furthermore, the weight ratio of the composition to water can be from 1:1 to 500. For example, the weight ratio of the alcoholysis composition (purified or purified and concentrated alcoholysis composition) used in hydrolysis to water can be from 1:1 to 450, 1:1 to 400, 1:1 to 250, 1:1 to 100, 1:1 to 50, 1:1.2 to 20, or 1:1.5 to 10.
[0129] Furthermore, in step (2), a hydrolysis catalyst may be added. Specifically, the hydrolysis catalyst may be added to the mixture of the alcoholysis reaction composition and water to carry out hydrolysis.
[0130] Hydrolysis can proceed smoothly as a non-catalytic reaction without the use of a hydrolysis catalyst, making it environmentally friendly. In particular, when the content of insoluble metals in waste polyester is high, non-catalytic reactions may be beneficial for the effective treatment and removal of impurities. Furthermore, from an energy perspective, a hydrolysis catalyst can be added in step (2) to improve processability by enhancing reactivity.
[0131] Hydrolysis catalysts can be metal acetates, alkali metal salts, or hydroxyl salts.
[0132] More specifically, the hydrolysis catalyst may contain at least one cation selected from the group consisting of alkali metal ions such as Li. + Na + K + and Cs + Alkaline earth metal ions such as Be 2+ Mg 2+ Ca 2+ and Ba 2+ Ammonium ions, such as NH4+ 4+ and NR 4 + (where R is an alkyl group), and Zn 2+ ; or at least one anion selected from the group consisting of: OH- - OR - (where R is an alkyl group), HCO3 - CO3 2- Benzoate ions (C7H5O2) -), 4-alkoxycarbonylbenzoate ion, acetate ion, and terephthalate ion. R can be an alkyl group having 1 to 10 carbon atoms or an alkyl group having 1 to 5 carbon atoms.
[0133] For example, the hydrolysis catalyst may contain at least one selected from the group consisting of: Zn(OAC)2, Co(OAc)2, Mn(OAc)2, Mg(OAc)2, Ca(OAc)2, Ba(OAc)2, LiOAc, NaOAc, KOAc, Zn(OAC)2·2H2O, Co(OAc)2·4H2O, Pb(OAc)2, Mn(OAc)2·4H2O, Mg(OAc)2·4H2O, Pd(OAc)2, Ti(OBu)4, Ti(OiPr)4, GeO2, Al(OiPr)3, Na2CO3, K2CO3, dibutyltin oxide (IV), stannous octoate, titanium phosphate, and terephthalic acid.
[0134] Furthermore, the amount of hydrolysis catalyst added can be from 10 ppm to 10,000 ppm, based on the total weight of the composition. For example, the amount of hydrolysis catalyst added can be from 15 ppm to 8,000 ppm, 20 ppm to 5,500 ppm, 30 ppm to 3,000 ppm, 50 ppm to 1,600 ppm, 100 ppm to 1,200 ppm, 150 ppm to 1,100 ppm, 300 ppm to 1,000 ppm, 350 ppm to 950 ppm, 400 ppm to 850 ppm, 420 ppm to 700 ppm, or 450 ppm to 650 ppm, based on the total weight of the alcoholysis composition (purified or purified and concentrated alcoholysis composition).
[0135] According to embodiments of the present invention, solid-recycled terephthalic acid can be prepared by a hydrolysis reaction. Specifically, the method may further include filtering, washing, and drying the hydrolysis product prepared by the hydrolysis reaction after the hydrolysis step. That is, the hydrolysis product prepared by the hydrolysis reaction can be filtered, washed, and dried to produce solid-recycled terephthalic acid.
[0136] For example, the hydrolysis product can be cooled to a suitable temperature at which water will not vaporize (e.g., from room temperature to below 100°C) to obtain a solution in slurry form, the solution can be filtered to obtain a solid, the solid can be washed and dried under vacuum to obtain solid recycled terephthalic acid.
[0137] Washing can be performed using a mixture of alcohols and / or water having four or more carbon atoms, protic solvents such as isopropanol and acetic acid, or aprotic solvents such as acetone, dichloromethane, chloroform, tetrahydrofuran (THF), and toluene.
[0138] Here, the description of alcohols having four or more carbon atoms is as described above. The alcohol with four or more carbon atoms used in the washing process may be the same as or different from the alcohol with four or more carbon atoms used in step (1). For example, when 1-butanol is used as the alcohol in step (1) to produce terephthalic acid, the prepared solid terephthalic acid may be washed with a mixture of 1-butanol and water. Furthermore, the number of carbon atoms of the alcohol used in the washing process may be the same as the number of carbon atoms of the alcohol used in step (1).
[0139] Washing effectively removes residual pigments or yellow impurities produced during pigment hydrolysis, thereby enhancing the yellowness index or chromaticity characteristics. Furthermore, washing with water removes mineral salts, thus improving quality.
[0140] Furthermore, the yield of recycled terephthalic acid can be 65% or more. For example, the final yield of recycled terephthalic acid produced can be 68% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more.
[0141] The step of mixing recycled terephthalic acid with the glycol component to prepare the preliminary composition.
[0142] A method for preparing a polyester resin according to another embodiment of the present invention includes: mixing recycled terephthalic acid with a glycol component to prepare a preliminary composition.
[0143] Furthermore, the diacid component may be further mixed during the preparation of the preliminary composition. Details regarding the diacid and diol components are as described above.
[0144] Furthermore, at least one additive selected from the group consisting of colorants, crystallizing agents, oxidative stabilizers, and branching agents may be added during the preparation of the preliminary composition. Details regarding the additives are as described above.
[0145] The step of esterification of the preparative composition
[0146] A method for preparing a polyester resin according to another embodiment of the present invention may further include esterification of a preparative composition.
[0147] Esterification can be carried out at temperatures ranging from 200°C to 350°C, 220°C to 320°C, or 250°C to 290°C. Furthermore, esterification can be carried out at pressures above atmospheric pressure (0 kg / cm²).2 Up to 10 kg / cm 2 (0 mmHg to 7,355.6 mmHg), 0 kg / cm 2 Up to 5kg / cm 2 (0 to 3,677.8 mmHg), or 0 kg / cm 2 Up to 2.0 kg / cm 2 The reaction is carried out under a pressure of 0 to 1,471.1 mmHg. Furthermore, the esterification reaction can be carried out for 1 to 24 hours, 1 to 10 hours, or 1 to 6 hours.
[0148] The step of polycondensation reaction of esterification products
[0149] A method for preparing a polyester resin according to another embodiment of the present invention includes performing a polycondensation reaction on the esterification reaction product.
[0150] Furthermore, the polycondensation reaction can be carried out at temperatures ranging from 150°C to 400°C, 200°C to 370°C, 250°C to 350°C, or 270°C to 300°C. Furthermore, the polycondensation reaction can be carried out under reduced pressures of 0.01 mmHg to 400 mmHg, 0.05 mmHg to 100 mmHg, or 0.1 mmHg to 100 mmHg. Furthermore, the polycondensation reaction can proceed for the desired time until the desired intrinsic viscosity is reached. For example, it can proceed from 1 hour to 24 hours, 1 hour to 10 hours, or 1 hour to 4 hours.
[0151] At the start of the polycondensation reaction, the stirring speed can be set relatively high. As the polycondensation reaction proceeds, if the stirring power is reduced due to the increase in the viscosity of the reactants or if the temperature of the reactants rises above the set temperature, the stirring speed can be adjusted accordingly.
[0152] Furthermore, catalysts and / or stabilizers can be added during esterification and polycondensation reactions.
[0153] For example, catalysts used for esterification reactions can be methoxides of sodium and magnesium; acetates, borates, fatty acid salts, and carbonates of Zn, Cd, Mn, Co, Ca, and Ba; metallic Mg; and oxides of Pb, Zn, Sb, Ge, and Ti.
[0154] Furthermore, the catalyst for the polycondensation reaction can be, for example, titanium-based catalysts such as tetraethyl titanate, tripropyl titanate, tetrapropyl titanate, tetrabutyl titanate, polybutyl titanate, 2-ethylhexyl titanate, octyl glycol titanate, lactate titanate, triethanolamine titanate, acetylacetone titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, titanium dioxide / silica copolymer, titanium dioxide / zirconium dioxide copolymer; germanium-based catalysts such as germanium dioxide and copolymers using germanium dioxide; or tin-based catalysts such as butyltin oxide, dibutyltin oxide, and butyl hydroxytin oxide.
[0155] In addition, stabilizers can be phosphorus-based compounds, such as phosphoric acid, trimethyl phosphate, and triethyl phosphate, but are not limited to these.
[0156] A method for preparing a polyester resin according to another embodiment of the present invention may further include carrying out a solid-state polymerization reaction. For example, the solid-state polymerization may be carried out after a polycondensation reaction at a temperature of 190°C to 230°C, under vacuum conditions of 0.2 Torr to 2.0 Torr, or under a nitrogen atmosphere.
[0157] The invention will be described in more detail below with reference to the following examples. However, these examples are set forth to illustrate the invention, and the scope of the invention is not limited thereto.
[0158] Embodiments of the present invention
[0159] [Example]
[0160] Preparation of liquid compositions
[0161] Example 1-1
[0162] 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as an alcohol were charged into a first high-pressure reactor with a capacity of 7 liters. Then, 200 mg (200 ppm relative to the total weight of waste PET) of Zn(OAC)2·2H2O was added as an alcoholysis catalyst.
[0163] Subsequently, with all connections in the first high-pressure reactor tightened and sealed, the temperature was raised to 250°C over 1 hour, and the alcoholysis reaction was carried out under stirring for 3 hours while maintaining a temperature of 250°C and a pressure of 24 bar.
[0164] After the alcoholysis reaction was completed, it was cooled to room temperature to obtain a liquid alcoholysis composition. Here, the components and contents of the alcoholysis composition were analyzed by NMR. The alcoholysis composition contained a compound represented by Formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.
[0165] Subsequently, the alcoholysis reaction composition was placed in a separate flask, and the excess unreacted 1-butanol and the generated ethylene glycol (EG) were recovered separately using a fractionation apparatus.
[0166] [Formula 1]
[0167] Example 1-2
[0168] 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as an alcohol were charged into a first high-pressure reactor with a capacity of 7 liters. Then, 200 mg (200 ppm relative to the total weight of waste PET) of Zn(OAC)2·2H2O was added as an alcoholysis catalyst.
[0169] Subsequently, with all connections in the first high-pressure reactor tightened and sealed, the temperature was raised to 250°C over 1 hour, and the alcoholysis reaction was carried out under stirring for 3 hours while maintaining a temperature of 250°C and a pressure of 24 bar.
[0170] Specifically, one hour after the start of the alcoholysis reaction, the valve of the pre-installed back pressure regulator is adjusted to discharge the gaseous mixture of ethylene glycol (EG), a byproduct of the alcoholysis reaction, and excess 1-butanol. In this case, the internal temperature of the first high-pressure reactor is maintained at 250°C, and the gaseous mixture of ethylene glycol (EG) and 1-butanol discharged through the back pressure regulator is condensed using an external cooling device. Furthermore, the discharge rate of the gaseous mixture of ethylene glycol (EG) and 1-butanol is adjusted to 3 kg / h, while 1-butanol is continuously supplied to the first high-pressure reactor simultaneously. In this case, the volume and feed rate of the newly supplied 1-butanol to the first high-pressure reactor are adjusted to be the same as the volume and discharge rate of the discharged gaseous mixture of ethylene glycol (EG) and 1-butanol. The alcoholysis reaction proceeds while the discharge and feeding process is maintained for 3 hours.
[0171] After the alcoholysis reaction was completed, it was cooled to room temperature to obtain a liquid alcoholysis composition. Here, the components and contents of the alcoholysis composition were analyzed by NMR. The alcoholysis composition contained a compound represented by Formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.
[0172] Subsequently, the alcoholysis reaction composition was placed in a separate flask, and the excess unreacted 1-butanol and the generated ethylene glycol were recovered separately using a fractionation apparatus.
[0173] [Formula 1]
[0174] Example 1-3
[0175] 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as an alcohol were charged into a first high-pressure reactor with a capacity of 7 liters. Then, 200 mg (200 ppm relative to the total weight of waste PET) of Zn(OAC)2·2H2O was added as an alcoholysis catalyst.
[0176] Subsequently, with all connections in the first high-pressure reactor tightened and sealed, the temperature was raised to 250°C over 1 hour, and the alcoholysis reaction was carried out under stirring for 3 hours while maintaining a temperature of 250°C and a pressure of 24 bar.
[0177] Specifically, one hour after the start of the alcoholysis reaction, the valve of the pre-installed back pressure regulator is adjusted to discharge the gaseous mixture of ethylene glycol (EG), a byproduct of the alcoholysis reaction, and excess 1-butanol. In this case, the internal temperature of the first high-pressure reactor is maintained at 250°C, and the gaseous mixture of ethylene glycol (EG) and 1-butanol discharged through the back pressure regulator is condensed using an external cooling device. Furthermore, the discharge rate of the gaseous mixture of ethylene glycol (EG) and 1-butanol is adjusted to 3 kg / h, while 1-butanol is continuously supplied to the first high-pressure reactor simultaneously. In this case, the volume and feed rate of the newly supplied 1-butanol to the first high-pressure reactor are adjusted to be the same as the volume and discharge rate of the discharged gaseous mixture of ethylene glycol (EG) and 1-butanol.
[0178] The condensed gaseous mixture of ethylene glycol (EG) and 1-butanol was transferred to a 5-liter layer separator filled with 3 kg of water. The process of stirring for 10 minutes and separating the layers for 2 minutes was repeated to separate the 1-butanol layer from the water and ethylene glycol (EG) layers. The separated 1-butanol was then fed back into the first high-pressure reactor in real-time using a high-pressure pump. The alcoholysis reaction was then carried out while maintaining stirring, layer separation, and reintroduction for 3 hours.
[0179] After the alcoholysis reaction was completed, it was cooled to room temperature to obtain a liquid alcoholysis composition. Here, the components and contents of the alcoholysis composition were analyzed by NMR. The alcoholysis composition contained a compound represented by Formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.
[0180] Subsequently, the alcoholysis reaction composition was placed in a separate flask, and the excess unreacted 1-butanol and the generated ethylene glycol were recovered separately using a fractionation apparatus.
[0181] [Formula 1]
[0182] Examples 1-4
[0183] The liquid alcoholysis reaction composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.
[0184] Examples 1-5
[0185] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.
[0186] Examples 1-6
[0187] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-3, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.
[0188] Examples 1-7
[0189] The liquid alcoholysis composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.
[0190] Examples 1-8
[0191] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.
[0192] Examples 1-9
[0193] Liquid alcoholysis reaction compositions were prepared in the same manner as in Examples 1-3, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.
[0194] Example 1-10
[0195] The liquid alcoholysis composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.
[0196] Example 1-11
[0197] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.
[0198] Example 1-12
[0199] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-3, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.
[0200] Example 1-13
[0201] The liquid alcoholysis composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 1-decyl alcohol was used as the alcohol and the pressure was maintained at 1.6 bar.
[0202] Example 1-14
[0203] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of 1-decyl alcohol was used as the alcohol and the pressure was maintained at 1.6 bar.
[0204] Example 1-15
[0205] Liquid alcoholysis reaction compositions were prepared in the same manner as in Examples 1-3, except that 3.3 kg of 1-decyl alcohol was used as the alcohol and the pressure was maintained at 1.6 bar.
[0206] Example 1-16
[0207] The liquid alcoholysis composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 1-dodecyl alcohol was used as the alcohol and the pressure was maintained at 1.0 bar.
[0208] Example 1-17
[0209] 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-dodecyl alcohol as an alcohol were charged into a first high-pressure reactor with a capacity of 7 liters. Then, 200 mg (200 ppm relative to the total weight of waste PET) of Zn(OAC)2·2H2O was added as an alcoholysis catalyst.
[0210] Subsequently, with all connections in the first high-pressure reactor tightened and sealed, the temperature was raised to 250°C over 1 hour, and the alcoholysis reaction was carried out under stirring for 3 hours while maintaining a temperature of 250°C and a pressure of 1.0 bar.
[0211] Specifically, one hour after the start of the alcoholysis reaction, the valve of the pre-installed back pressure regulator is adjusted to release the vapor of ethylene glycol (EG), a byproduct of the alcoholysis reaction. In this case, the internal temperature of the first high-pressure reactor is maintained at 250°C, and the ethylene glycol (EG) vapor is condensed using an external cooling device.
[0212] In addition, 1-dodecyl alcohol is continuously supplied to the first high-pressure reactor in an amount equal to that of ethylene glycol (EG) that is discharged as vapor and condensed. In this case, the volume and feed rate of the newly supplied 1-dodecyl alcohol to the first high-pressure reactor are adjusted to be the same as the volume and discharge rate of the discharged ethylene glycol (EG) vapor. The alcoholysis reaction is carried out while the discharge and feed processes are maintained for 3 hours.
[0213] After the alcoholysis reaction was completed, it was cooled to room temperature to obtain a liquid alcoholysis composition. Here, the components and contents of the alcoholysis composition were analyzed by NMR. The alcoholysis composition contained a compound represented by Formula 1 (R1: (CH2)). 11 CH3), residual ethylene glycol (EG), alcohol (1-dodecyl alcohol) and oligomers.
[0214] Subsequently, the alcoholysis reaction composition was placed in a separate flask, and the excess unreacted 1-dodecyl alcohol and the generated ethylene glycol (EG) were recovered separately using a fractionation apparatus.
[0215] [Formula 1]
[0216] Example 1-18
[0217] The liquid alcoholysis composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of 1-tetradecaneol was used as the alcohol and the pressure was maintained at 1.0 bar.
[0218] Example 1-19
[0219] Liquid alcoholysis reaction compositions were prepared in the same manner as in Examples 1-17, except that 3.3 kg of 1-tetradecyl alcohol was used as the alcohol.
[0220] Comparison Example 1-1
[0221] The liquid alcoholysis reaction composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of methanol was used as the alcohol and the pressure was maintained at 83 bar.
[0222] Comparison Examples 1-2
[0223] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of methanol was used as the alcohol and the pressure was maintained at 83 bar.
[0224] Comparison Examples 1-3
[0225] The liquid alcoholysis reaction composition was prepared in the same manner as in Example 1-1, except that 3.3 kg of ethanol was used as the alcohol and the pressure was maintained at 64 bar.
[0226] Comparison Examples 1-4
[0227] The liquid alcoholysis reaction composition was prepared in the same manner as in Examples 1-2, except that 3.3 kg of ethanol was used as the alcohol and the pressure was maintained at 64 bar.
[0228] [Table 1]
[0229] As can be seen from Table 1 above, since the liquid alcoholysis compositions of Examples 1-1 to 1-19 are prepared using alcohols having four or more carbon atoms, they can be prepared under very low process pressures compared to Comparative Examples 1-1 to 1-4. The compounds represented by Formula 1 have high content, i.e., high yield and purity, and the recovery rate of ethylene glycol is also excellent.
[0230] Purification and concentration of liquid compositions
[0231] Example 2-1
[0232] Before using a fractionation apparatus to recover excess unreacted alcohol and produced ethylene glycol in Example 1-1, 0.1 g of activated carbon as an adsorbent was added to 100 g of liquid alcoholysis composition, which was then purified, stirred at 100°C for 3 hours, and then filtered to concentrate the alcoholysis composition.
[0233] Examples 2-2 to 2-23 and comparison examples 2-1 and 2-2
[0234] The liquid alcoholysis reaction composition was purified and concentrated in the same manner as in Example 2-1, except that the liquid composition and process conditions were changed as shown in Table 2 below. Here, in Comparative Examples 2-1 and 2-2, it was not purified because it precipitated in an undissolved state.
[0235] Examples 2-24 to 2-26
[0236] After recovering excess unreacted alcohol and produced ethylene glycol using a fractionation apparatus in each of Examples 1-1, 1-4, and 1-10, 0.1 g of activated carbon as an adsorbent was added to 100 g of liquid alcoholysis composition, which was then purified, stirred at 100°C for 3 hours, and then filtered to concentrate the alcoholysis composition.
[0237] Compare Examples 2-3 to 2-21
[0238] Before using a fractionation apparatus to recover excess unreacted alcohol and produced ethylene glycol in each of Examples 1-1 to 1-19, no adsorbent is added to the liquid alcoholysis reaction composition, the mixture is stirred at 100°C for 3 hours, and then filtered to concentrate it.
[0239] Test Example 1-1: Pigment Residue Rate
[0240] Pigment residue (%) of the compositions in Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 were measured respectively.
[0241] Specifically, the composition of Example 2-1 was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and methylpyrrolidone (NMP), respectively, and the area of the absorbance curve (A1) was obtained using a UV-vis spectrophotometer from 400 nm to 800 nm. Furthermore, for the compositions of Comparative Examples 2-3 (the compositions of Example 1-1 were used in the same manner as those of Example 2-1, but without purification and concentration by adding an adsorbent), the area of the absorbance curve (A2) was obtained from 400 nm to 800 nm in the same manner as described above. The pigment residue (%) was calculated using the measured area of the absorbance curve according to Equation A below.
[0242] [Equation A]
[0243] In the same manner as described above, the pigment residue rate (%) of the compositions of Examples 2-2 to 2-26 and Comparative Examples 2-1 to 2-21 was measured respectively.
[0244] Test Example 1-2: Yellowness Index
[0245] The yellowness index (YI) of the compositions in Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 was measured respectively.
[0246] Specifically, the compositions of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 were diluted to a concentration of 5% in a solvent, and the yellowness index was measured using a ColorFlex EZ device (manufacturer: HunterLab). In this case, the solvent used was dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP).
[0247] Test Examples 1-3: Metal Content
[0248] The metal content (ppm) in each composition of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 was measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). Here, ND indicates that the content was too low (less than 1 ppm) to be measured as a specific value.
[0249] [Table 2]
[0250] As can be seen from Table 2 above, the purified and concentrated alcoholysis compositions of Examples 2-1 to 2-26 have very low pigment residue and very low metal (such as Sb, Ti and Zn) content.
[0251] Preparation of recycled terephthalic acid
[0252] Example 3-1
[0253] 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml. Then, 50 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis reaction composition) of Zn(OAC)2·2H2O was added to it.
[0254] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C while the hydrolysis reaction was carried out for 4 hours. The reactor was then cooled to 90°C to obtain a slurry of the hydrolysis product. The slurry was filtered to obtain a solid, which was washed with butanol and water at 90°C and dried under vacuum to obtain 53.7 g (yield: 90%) of recycled terephthalic acid (TPA).
[0255] Example 3-2
[0256] 100 g (0.30 mol) of the purified and concentrated alcoholysis reaction composition of Examples 2-5 and 200 g (11.10 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml. Then, 50 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis reaction composition) of Zn(OAC)2·2H2O was added to it.
[0257] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C while the hydrolysis reaction was carried out for 4 hours. The reactor was then cooled to 90°C to obtain a slurry of the hydrolysis product. The slurry was filtered to obtain a solid, which was washed with pentanol and water at 90°C and dried under vacuum to obtain 43.9 g (yield: 81%) of recycled terephthalic acid (TPA).
[0258] Example 3-3
[0259] 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-11 and 1,000 g (55.50 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml, and then 50 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis reaction composition) of Zn(OAC)2·2H2O was added.
[0260] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C while the hydrolysis reaction was carried out for 4 hours. The reactor was then cooled to 90°C to obtain a slurry of the hydrolysis product. The slurry was filtered to obtain a solid, which was washed with 2-ethyl-1-hexanol and water at 90°C and dried under vacuum to obtain 38.0 g (yield: 88%) of recycled terephthalic acid (TPA).
[0261] Example 3-4
[0262] 35.4 g (yield: 82%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Examples 3-3, except that 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Examples 2-13 was used.
[0263] Example 3-5
[0264] 36.7 g (yield: 85%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Examples 3-3, except that 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Examples 2-14 was used.
[0265] Example 3-6
[0266] 114 g (0.26 mol) of the purified and concentrated alcoholysis composition of Example 2-18 and 200 g (11.10 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml, followed by the addition of 57 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis composition) of Zn(OAC)2·2H2O.
[0267] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C while the hydrolysis reaction was carried out for 4 hours. The reactor was then cooled to 90°C to obtain a slurry of the hydrolysis product. The slurry was filtered to obtain a solid, which was washed with decanol and water at 90°C and dried under vacuum to obtain 36.1 g (yield: 85%) of recycled terephthalic acid (TPA).
[0268] Example 3-7
[0269] 54.3 g (yield: 91%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Example 3-1, except that no hydrolysis catalyst was added.
[0270] Example 3-8
[0271] 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml. Then, 50 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis reaction composition) of Zn(OAC)2·2H2O was added to it.
[0272] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C for 4 hours while the hydrolysis reaction was carried out. The mixture was then cooled to 90°C to obtain the hydrolysis product in slurry form. Acetone was added to the solid obtained by filtering the slurry hydrolysis product, followed by stirring at 50°C for 4 hours. This was filtered, washed with acetone and water at 50°C, and dried under vacuum to obtain 55.6 g (yield: 93%) of solid recycled terephthalic acid (TPA).
[0273] Example 3-9
[0274] 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged into a second high-pressure reactor with a capacity of 600 ml. Then, 50 mg (500 ppm relative to the total weight of the purified and concentrated alcoholysis reaction composition) of Zn(OAC)2·2H2O was added to it.
[0275] Subsequently, the temperature of the second high-pressure reactor was raised to 260°C and maintained at 260°C while the hydrolysis reaction was carried out for 4 hours, followed by cooling to 90°C to obtain the hydrolysis product in slurry form. Butanol was added to the solid obtained by filtering the slurry hydrolysis product, followed by stirring at 90°C for 4 hours. It was then filtered, washed with butanol and water at 50°C, and dried under vacuum to obtain 53.1 g (yield: 89%) of solid recycled terephthalic acid (TPA).
[0276] Example 3-10
[0277] 59.2 g (yield: 99%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Example 3-1, except that the filtrate separated by the filtration step in Example 3-1 was further used.
[0278] Specifically, the filtrate separated by the filtration step in Example 3-1 was again loaded into the second high-pressure reactor, the temperature was raised to 260°C, and the hydrolysis reaction was carried out at 260°C for 4 hours. The mixture was then cooled to 90°C to obtain a hydrolysis product in slurry form. The slurry-like hydrolysis product was filtered to obtain a solid, which was washed with butanol and water at 90°C and dried under vacuum to further obtain 5.5 g of solid recycled terephthalic acid (TPA).
[0279] Comparative Example 3-1
[0280] 54.4 g (yield: 91%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Example 3-1, except that 100 g (0.36 mol) of the composition of Comparative Examples 2-4 was used.
[0281] Comparative Example 3-2
[0282] 40.4 g (yield: 81%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Examples 3-2, except that 100 g (0.30 mol) of the composition of Comparative Examples 2-7 was used.
[0283] Comparative Example 3-3
[0284] 36.7 g (yield: 85%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Examples 3-3, except that 100 g (0.26 mol) of the composition of Comparative Examples 2-13 was used.
[0285] Comparative Examples 3-4
[0286] 34.4 g (yield: 81%) of solid recycled terephthalic acid (TPA) was obtained in the same manner as in Examples 3-6, except that 114 g (0.26 mol) of the composition of Comparative Examples 2-16 was used.
[0287] Test Example 2-1: Pigment Residue Rate
[0288] The pigment residue rate (%) of terephthalic acid in each of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4 was measured.
[0289] Specifically, the terephthalic acid of Example 3-1 was diluted to a concentration of 5% in a solvent, and the area of the absorbance curve (B1) was obtained using a UV-vis spectrophotometer from 400 nm to 800 nm. In this case, the solvent used was dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP). Furthermore, for the compositions of Comparative Examples 2-4 (which used the compositions of Examples 1-2 used in the preparation of the terephthalic acid of Example 3-1, but which were concentrated without the addition of an adsorbent), the area of the absorbance curve (B2) from 400 nm to 800 nm was obtained in the same manner as described above. The pigment residue (%) was calculated using the measured area of the absorbance curve according to Equation B below.
[0290] [Equation B]
[0291] The pigment residue rate (%) of terephthalic acid in Examples 3-2 to 3-10 and Comparative Examples 3-1 to 3-4 was measured in the same manner as described above. Specifically, for B2 of Formula 1 above, the composition of Comparative Examples 2-7 was used to measure Example 3-2, the composition of Comparative Examples 2-13 was used to measure Example 3-3 to 3-5, and the composition of Comparative Examples 2-16 was used to measure Example 3-6. Furthermore, in Comparative Examples 3-1 to 3-4, the composition of Comparative Examples 2-4, 2-7, 2-13, and 2-16 was used to measure B2 of Formula 1, respectively.
[0292] Test Example 2-2: Yellowness Index
[0293] The yellowness index (YI) of recycled terephthalic acid was measured in Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4.
[0294] Specifically, the recycled terephthalic acid in each of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4 was diluted to a concentration of 5% in a solvent, and the yellowness index was measured using a ColorFlex EZ device (manufacturer: Huntley Company). In this case, the solvent used was dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP).
[0295] Test Example 2-3: Metal Content
[0296] The metal content (ppm) in terephthalic acid in Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-10 was measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). Here, ND indicates that the content was too low (less than 1 ppm) to be measured as a specific value.
[0297] Test Example 2-4: Chromaticity b
[0298] The colorimetric b (colorimetric characteristic) of terephthalic acid in Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4 was measured using a spectrophotometer.
[0299] Specifically, a Varian Cary 5 UV / Vis / NIR spectrophotometer equipped with a diffuse reflectance accessory capable of measuring chromaticity and lightness was used to measure recycled terephthalic acid in reflectance mode with a luminescent element of D65 and an observation angle of 2° to obtain data, which was then processed by the chromaticity analysis device in Grams / 32 software to calculate the chromaticity b value.
[0300] [Table 3]
[0301] As can be seen from Table 3 above, the recycled terephthalic acid prepared in Examples 3-1 to 3-6 not only has low pigment residue and low yellowness index, and meets a specific range of chromaticity b values, but also has very low metal (as impurity) content. In particular, in Example 3-10, recycled terephthalic acid was obtained in a very high yield using the filtrate separated by the filtration step, i.e., the unreacted material.
[0302] Preparation of polyester resin
[0303] Example 4-1
[0304] (a) Preparation of the preliminary composition
[0305] The recycled terephthalic acid (r-TPA, 5,810.6 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 3,810.4 g), ethylene glycol (EG, 1,333.1 g), cyclohexanediol (CHDM, 864.1 g), isosorbide (ISB, 292.0 g), and diethylene glycol (DEG, 73.0 g) prepared in Example 3-1 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycols / total diacids; molar ratio of glycols to diacids) was 1.2.
[0306] Subsequently, 12.8 g of Ge catalyst, 10.0 g of phosphoric acid as a stabilizer, 0.010 g of blue toner, 0.005 g of red toner, and 1,000 ppm of hindered phenol-based oxidation stabilizer (product name: Irganox1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0307] (b) Esterification reaction
[0308] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 1.0 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,495.6 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0309] (c) Condensation polymerization
[0310] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 270°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.70 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0311] (d) Solid-state polymerization reaction
[0312] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 200°C at a rate of 40°C / hour and maintained at 200°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 1.30 dl / g to prepare the polyester resin.
[0313] Example 4-2
[0314] (a) Preparation of the preliminary composition
[0315] The recycled terephthalic acid (r-TPA, 8,419.6 g), ethylene glycol (EG, 6,341.7 g), cyclohexanediol (CHDM, 365.2 g), isosorbide (ISB, 98.7 g), and diethylene glycol (DEG, 148.1 g) prepared in Example 3-2 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycols / total diacids; molar ratio of glycols to diacids) was 2.1.
[0316] Subsequently, 6.4 g of Ge catalyst, 0.030 g of blue toner and 0.015 g of red toner were added, and the mixture was stirred to prepare a preliminary composition.
[0317] (b) Esterification reaction
[0318] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 2.0 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 2,231.2 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0319] (c) Condensation polymerization
[0320] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 280°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.60 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0321] (d) Solid-state polymerization reaction
[0322] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 210°C at a rate of 40°C / hour and maintained at 210°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 0.85 dl / g to prepare the polyester resin.
[0323] Example 4-3
[0324] (a) Preparation of the preliminary composition
[0325] The recycled terephthalic acid (r-TPA, 4,195.3 g), terephthalic acid (TPA, 4,195.3 g), ethylene glycol (EG, 4,794.8 g), cyclohexanediol (CHDM, 145.6 g), and diethylene glycol (DEG, 369.0 g) prepared in Example 3-3 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 1.6, and the molar ratio of r-TPA to TPA was 1:1.
[0326] Subsequently, 6.4 g of Ge catalyst, 0.9 g of Ti catalyst, 1.0 g of phosphoric acid as a stabilizer, 0.040 g of blue toner, 0.010 g of red toner, and 100 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0327] (b) Esterification reaction
[0328] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 0.5 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,127.8 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0329] (c) Condensation polymerization
[0330] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 275°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.70 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0331] Example 4-4
[0332] (a) Preparation of the preliminary composition
[0333] The recycled terephthalic acid (r-TPA, 2,486.5 g), terephthalic acid (TPA, 4,973.0 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 1,268.2 g), ethylene glycol (EG, 2,600.4 g), cyclohexanediol (CHDM, 431.4 g), and diethylene glycol (DEG, 364.5 g) prepared in Examples 3-4 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 1.15, and the molar ratio of r-TPA to TPA was 1:2.
[0334] Subsequently, 0.4 g of Ti catalyst, 2.0 g of phosphoric acid as a stabilizer, 2.1 g of cobalt acetate as a colorant, and 200 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0335] (b) Esterification reaction
[0336] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 1.0 kgf / cm² above atmospheric pressure. 2(Absolute pressure: 1,495.6 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 250°C over 2 hours. The esterification reaction was then carried out at 250°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0337] (c) Condensation polymerization
[0338] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 265°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.60 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0339] (d) Solid-state polymerization reaction
[0340] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 220°C at a rate of 40°C / hour and maintained at 220°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 1.00 dl / g to prepare the polyester resin.
[0341] Example 4-5
[0342] (a) Preparation of the preliminary composition
[0343] The recycled terephthalic acid (r-TPA, 754.8 g), terephthalic acid (TPA, 1,887.0 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 7,507.3 g), ethylene glycol (EG, 1,268.6 g), cyclohexanediethanol (CHDM, 2,095.3 g), and a compound comprising 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol in a 1:3 molar ratio were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A (total glycol / total diacid; molar ratio of glycol component to diacid component) is 2.1, and the molar ratio of r-TPA to TPA is 1:2.5.
[0344] Subsequently, 12.8 g of Ge catalyst, 0.9 g of Ti catalyst, 1.0 g of phosphoric acid as a stabilizer, 1.3 g of cobalt acetate as a colorant, 0.006 g of blue toner, 0.002 g of red toner, and 100 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0345] (b) Esterification reaction
[0346] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 2.0 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 2,231.2 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 255°C over 2 hours. The esterification reaction was then carried out at 255°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0347] (c) Condensation polymerization
[0348] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 285°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.78 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0349] Example 4-6
[0350] (a) Preparation of the preliminary composition
[0351] The recycled terephthalic acid (r-TPA, 6,640.6 g), terephthalic acid (TPA, 368.9 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 564.5 g), ethylene glycol (EG, 3,279.4 g), cyclohexanediol (CHDM, 1,984.2 g), and diethylene glycol (DEG, 648.9 g) prepared in Examples 3-6 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 1.7, and the molar ratio of r-TPA to TPA was 1:0.05.
[0352] Subsequently, 0.2 g of Ti catalyst, 2.0 g of phosphoric acid as a stabilizer, 2.7 g of cobalt acetate as a colorant, and 200 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0353] (b) Esterification reaction
[0354] Subsequently, nitrogen gas was injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 1.5 kgf / cm² above atmospheric pressure. 2(Absolute pressure: 1,863.4 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 250°C over 2 hours. The esterification reaction was then carried out at 250°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0355] (c) Condensation polymerization
[0356] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 270°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.82 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0357] Example 4-7
[0358] (a) Preparation of the preliminary composition
[0359] The recycled terephthalic acid (r-TPA, 5,958.1 g), terephthalic acid (TPA, 1,051.4 g), ethylene glycol (EG, 898.9 g), cyclohexanediol (CHDM, 4,256.4 g), isosorbide (ISB, 1,890.6 g), and diethylene glycol (DEG, 616.5 g) prepared in Examples 3-7 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 1.45, and the molar ratio of r-TPA to TPA was 1:0.18.
[0360] Subsequently, 64.0 g of Ge catalyst, 0.2 g of phosphoric acid as a stabilizer, 0.030 g of blue toner, 0.010 g of red toner, and 20 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0361] (b) Esterification reaction
[0362] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 1.0 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,495.6 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 265°C over 2 hours. The esterification reaction was then carried out at 265°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0363] (c) Condensation polymerization
[0364] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 275°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.70 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0365] Example 4-8
[0366] (a) Preparation of the preliminary composition
[0367] The recycled terephthalic acid (r-TPA, 1,545.8 g), terephthalic acid (TPA, 3,864.4 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 3,547.8 g), ethylene glycol (EG, 721.7 g), cyclohexanediethanol (CHDM, 536.4 g), diethylene glycol (DEG, 747.7 g), and a compound (407.9 g) comprising 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol in a 1:3 molar ratio were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, G / A (total diol / total diacid; molar ratio of diol component to diacid component) is 1.1, and the molar ratio of r-TPA to TPA is 1 : 2.51.
[0368] Subsequently, 6.4 g of Ge catalyst, 1.0 g of phosphoric acid as a stabilizer, 0.050 g of blue toner, 0.020 g of red toner, and 100 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0369] (b) Esterification reaction
[0370] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 0.5 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,127.8 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0371] (c) Condensation polymerization
[0372] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 275°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.75 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0373] Example 4-9
[0374] (a) Preparation of the preliminary composition
[0375] The recycled terephthalic acid (r-TPA, 3,788.8 g), terephthalic acid (TPA, 421.0 g), isophthalic acid (IPA, 7,998.6 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 6,441.5 g), ethylene glycol (EG, 3,102.7 g), cyclohexanediol (CHDM, 365.2 g), isosorbide (ISB, 98.7 g), and diethylene glycol (DEG, 370.3 g) prepared in Examples 3-9 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 2.1, and the molar ratio of r-TPA to TPA was 1:0.11.
[0376] Subsequently, 0.9 g of Ti catalyst, 20.0 g of phosphoric acid as a stabilizer, 1.7 g of cobalt acetate as a colorant, and 2,000 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0377] (b) Esterification reaction
[0378] Subsequently, nitrogen gas was injected into the reactor containing the preparative composition of step (a) to increase the pressure in the reactor by 3.0 kgf / cm² above atmospheric pressure. 2(Absolute pressure: 2,966.8 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by another 2 hours at 260°C. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0379] (c) Condensation polymerization
[0380] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 280°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.60 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0381] (d) Solid-state polymerization reaction
[0382] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 190°C at a rate of 40°C / hour and maintained at 190°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 1.10 dl / g to prepare the polyester resin.
[0383] Comparison Example 4-1
[0384] (a) Preparation of the preliminary composition
[0385] The recycled terephthalic acid (r-TPA, 2,571.8 g), terephthalic acid (TPA, 2,571.8 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 5,246.8 g), ethylene glycol (EG, 2,134.5 g), cyclohexanediol (CHDM, 148.7 g), and isosorbide (ISB, 105.5 g) prepared in Comparative Example 3-1 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 1.6, and the molar ratio of r-TPA to TPA was 1:1.
[0386] Subsequently, 12.8 g of Ge catalyst was added, and the mixture was stirred to prepare a preliminary composition.
[0387] (b) Esterification reaction
[0388] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 0.5 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,127.8 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0389] (c) Condensation polymerization
[0390] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 280°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.50 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0391] (d) Solid-state polymerization reaction
[0392] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 200°C at a rate of 40°C / hour and maintained at 200°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 0.70 dl / g to prepare the polyester resin.
[0393] Comparison Example 4-2
[0394] (a) Preparation of the preliminary composition
[0395] The recycled terephthalic acid (r-TPA, 825.7 g), terephthalic acid (TPA, 5,367.1 g), recycled bis(2-hydroxyethyl) terephthalate (r-BHET, 3,158.6 g), ethylene glycol (EG, 5,746.5 g), cyclohexanediol (CHDM, 716.3 g), isosorbide (ISB, 193.7 g), and diethylene glycol (DEG, 72.6 g) prepared in Comparative Example 3-2 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycol / total diacid; molar ratio of glycol to diacid components) was 2.5, and the molar ratio of r-TPA to TPA was 1:6.46.
[0396] Subsequently, 0.4 g of Ti catalyst, 1.7 g of cobalt acetate as a colorant, and 10 ppm of hindered phenol-based oxidation stabilizer (trade name: Irganox 1076, manufacturer: BASF) were added, and the mixture was stirred to prepare a preliminary composition.
[0397] (b) Esterification reaction
[0398] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 1.0 kgf / cm² above atmospheric pressure. 2(Absolute pressure: 1,495.6 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 260°C over 2 hours. The esterification reaction was then carried out at 260°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0399] (c) Condensation polymerization
[0400] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 280°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.70 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg.
[0401] (d) Solid-state polymerization reaction
[0402] Subsequently, the particles from step (c) were placed at 150°C for 1 hour to crystallize, and then fed into a 20-liter reactor for solid-state polymerization. Nitrogen gas was then introduced into the reactor at a rate of 50 liters / minute. Under these conditions, the reactor temperature was increased from room temperature to 140°C at a rate of 40°C / hour and maintained at 140°C for 3 hours, and then increased to 200°C at a rate of 40°C / hour and maintained at 200°C. Solid-state polymerization continued until the intrinsic viscosity (IV) of the particles in the reactor reached 0.95 dl / g to prepare the polyester resin.
[0403] Comparative Example 4-3
[0404] (a) Preparation of the preliminary composition
[0405] The recycled terephthalic acid (r-TPA, 7,098.9 g), ethylene glycol (EG, 2,854.7 g), cyclohexanediol (CHDM, 3,079.0 g), isosorbide (ISB, 83.2 g), and diethylene glycol (DEG, 62.4 g) prepared in Comparative Example 3-3 were charged into a 10-liter reactor equipped with a tower and a water-coolable condenser. Here, the G / A ratio (total glycols / total diacids; molar ratio of glycols to diacids) was 1.6.
[0406] Subsequently, 6.4 g of Ge catalyst, 0.1 g of phosphoric acid as a stabilizer, 0.030 g of blue toner and 0.010 g of red toner were added, and the mixture was stirred to prepare a preliminary composition.
[0407] (b) Esterification reaction
[0408] Subsequently, nitrogen gas is injected into the reactor containing the preparative composition from step (a) to increase the pressure in the reactor by 0.5 kgf / cm² above atmospheric pressure. 2 (Absolute pressure: 1,127.8 mmHg). The reactor temperature was then raised from room temperature to 220°C over 90 minutes and maintained at 220°C for 2 hours, followed by a second raising to 255°C over 2 hours. The esterification reaction was then carried out at 255°C for 3 hours until the prepared composition became transparent, while the prepared composition in the reactor was visually observed. After the esterification reaction was complete, nitrogen gas in the pressurized reactor was vented to reduce the pressure in the reactor to atmospheric pressure, and the esterification product in the reactor was then transferred to a 7-liter reactor capable of reacting under vacuum.
[0409] (c) Condensation polymerization
[0410] Subsequently, the pressure of the reactor containing the esterification product from step (b) was reduced from atmospheric pressure to 5.0 Torr (absolute pressure: 5 mmHg) over 30 minutes. Simultaneously, the reactor temperature was raised to 280°C over 1 hour, and polycondensation was carried out while maintaining the reactor pressure at 1.0 Torr (absolute pressure: 1.0 mmHg) or lower. Here, the stirring speed was set relatively high at the start of the polycondensation reaction. As the polycondensation reaction proceeded, the stirring speed was appropriately adjusted accordingly when the stirring power decreased due to the increase in viscosity of the mixture in the reactor or when the temperature of the mixture rose above the set temperature. The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reached 0.60 dl / g. The mixture was then discharged outside the reactor to form strips, which were solidified with a cooling liquid and then granulated to have an average weight of approximately 12 mg to 14 mg to prepare the polyester resin.
[0411] Test Example 3-1: Composition of Polyester Resin
[0412] The polyester resins of Examples 4-1 to 4-9, as well as Comparative Examples 4-1 and 4-3, were dissolved in CDCl3 solvent at a concentration of 3 mg / ml. The composition (in molar percentage) of the polyester resins was then measured using 1H-NMR spectra obtained at 25°C using a nuclear magnetic resonance spectrometer (JEOL, 600 MHz FT-NMR).
[0413] Test Example 3-2: Chromaticity Characteristics
[0414] The chromaticity b and chromaticity L (color characteristics) of the polyester resins in Examples 4-1 to 4-9 and Comparative Examples 4-1 to 4-3 were measured using a spectrophotometer. Then, the difference between the chromaticity L value and the chromaticity b value was calculated, i.e., chromaticity L - chromaticity b value.
[0415] Specifically, polyester resin samples with a thickness of 6 mm were prepared. Using a Varian Cary 5 UV / Vis / NIR spectrophotometer equipped with a diffuse reflectance accessory capable of measuring chromaticity and lightness, the sample was measured in transmission mode with a luminescent element at D65 and an observation angle of 2° to obtain data. The data were then processed using the chromaticity analysis function in Grams / 32 software to calculate the Henry chromaticity L, chromaticity a, and chromaticity b values. The difference between the chromaticity L and chromaticity b values, i.e., chromaticity L - chromaticity b, was then calculated.
[0416] [Table 4]
[0417] As can be seen from Table 4 above, although the polyester resins of Examples 4-1 to 4-9 each contain recycled terephthalic acid (r-TPA) prepared from waste polyester, they all exhibit excellent color characteristics. Specifically, since the polyester resins of Examples 4-1 to 4-9 each contain recycled terephthalic acid from Examples 3-1 to 3-9, which has excellent color characteristics due to its low pigment residue, low yellowness index, and very low metal impurity content, these polyester resins have excellent quality. In particular, although the polyester resin of Example 2 has a high recycled terephthalic acid content of 42% by weight, without the additional use of terephthalic acid, it still exhibits excellent color characteristics.
Claims
1. A recycled terephthalic acid obtained by alcoholysis and hydrolysis of waste polyester and having a chromaticity b of less than 2 as measured in reflectance mode of a spectrophotometer.
2. The recycled terephthalic acid as described in claim 1, wherein, When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the recycled terephthalic acid had a total metal content of less than 100 ppm.
3. The recycled terephthalic acid as described in claim 1, wherein, When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the recycled terephthalic acid had a total content of less than 30 ppm of Sb, Ti and Zn.
4. The recycled terephthalic acid as described in claim 1, wherein, The recycled terephthalic acid is obtained through a purification process and has a pigment residue of 10% or less according to Equation 1 below: [Equation 1] In Equation 1, B1 is the area of the absorbance curve obtained using a UV-Vis spectrophotometer at 400 nm to 800 nm after diluting the recycled terephthalic acid to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or methylpyrrolidone (NMP). B2 is the area of the absorbance curve obtained in the same manner as above for recycled terephthalic acid obtained through the same preparation process but without purification.
5. The recycled terephthalic acid as described in claim 1, wherein, When the recycled terephthalic acid was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and methylpyrrolidone (NMP), and measured using a spectrophotometer, the yellowness index (YI) was less than 2.
6. A polyester resin comprising recycled terephthalic acid obtained by alcoholysis and hydrolysis of waste polyester and having a chromaticity b of less than 2 as measured in reflectance mode on a spectrophotometer, and The polyester resin has a difference between the chromaticity L value and the chromaticity b value (chromaticity L - chromaticity b) greater than 83 for a sample with a thickness of 6 mm, as measured in transmission mode of a spectrophotometer.
7. The polyester resin of claim 6, wherein, The content of recycled terephthalic acid is 0.1% to 55% by weight based on the total weight of the polyester resin.
8. The polyester resin as described in claim 6, wherein, This polyester resin contains a diacid component and a diol component. The diacid component comprises at least one selected from the group consisting of: terephthalic acid (TPA), isophthalic acid (IPA), dimethyl isophthalate, bis(2-hydroxyethyl) terephthalate, recycled bis(2-hydroxyethyl) terephthalate (r-BHET), phthalic acid, dimethyl terephthalate, phthalic anhydride, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylic acid, biphenyl dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, dimethyl 1,4-cyclohexanedicarboxylic acid, dimethyl 1,3-cyclohexanedicarboxylic acid, sebacic acid, succinic acid, isodecanedioic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid, and azelaic acid; and The diol compound comprises at least one selected from the group consisting of: isosorbide (ISB), recycled isosorbide (r-ISB), ethylene glycol (EG), recycled ethylene glycol (r-EG), 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-methylene-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-isopropyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-Butanediol, 2,3-Butanediol, 3-Methyl-1,5-pentanediol, 3-Methyl-2,4-pentanediol, 1,6-Hexanediol, 1,2-Cyclohexanediol, 1,4-Cyclohexanediol, cyclohexanediol (CHDM) and its derivatives, recycled cyclohexanediol (r-CHDM), diethylene glycol (DEG), recycled diethylene glycol (r-DEG), neopentyl glycol (NPG) and recycled neopentyl glycol (r-NPG).
9. The polyester resin of claim 8, wherein, The molar ratio of the recycled terephthalic acid to the diacid component is from 1:0.01 to 3.
5.
10. The polyester resin of claim 6, wherein, The polyester resin has an intrinsic viscosity (IV) of 0.5 dl / g to 1.3 dl / g.
11. An article comprising the polyester resin as described in claim 6.
12. A method for preparing a polyester resin, comprising: Waste polyester is alcoholized and hydrolyzed to prepare recycled terephthalic acid; The recycled terephthalic acid was mixed with the glycol component to prepare a preliminary composition; The preparative composition was subjected to an esterification reaction; as well as The esterification product was subjected to a polycondensation reaction. The recycled terephthalic acid has a chromaticity b of less than 2, as measured in reflectance mode on a spectrophotometer.
13. The method for preparing polyester resin according to claim 12, wherein, The diacid component is further mixed in the step of preparing the preparative composition.
14. The method for preparing polyester resin according to claim 12, wherein, The steps for preparing this preliminary composition include: (1) Alcohololysis of waste polyester with an alcohol having four or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1; and (2) Hydrolyze the liquid composition: [Formula 1] In Formula 1, R1 is an alkyl group having four or more carbon atoms.
15. The method for preparing polyester resin as described in claim 14, wherein, The alcohol has 4 to 14 carbon atoms.
16. The method for preparing a polyester resin as described in claim 14, further comprising purifying the liquid composition prior to step (2).
17. The method for preparing polyester resin as described in claim 16, wherein, The purification step includes adding at least one adsorbent selected from the group consisting of activated carbon, silica gel, alumina, zeolite and activated clay, or adsorbing by bed adsorption, and the amount of the added adsorbent is from 0.1% to 20% by weight based on the total weight of the liquid composition.